Web2forDev: An evolving vision [Development Gateway] - Primo Braga, Carlos A.; Popescu, Denisa (Technical Centre for Agricultural and Rural Cooperation, 2007)
Development Gateway has changed significantly in response to external challenges and the emergence of new web-based technologies